Estrategias de marketing digital para el mejoramiento de la promoción de las mipymes agrícolas de El Oro en el mercado internacional. - Ajila Aguilar, Ricardo Aaron; Cuenca Villacres, Nathalia Lissette (Machala : Universidad Técnica de Machala, 2022)
Despite the fact that the internationalization process for MSMEs is not easy, because it includes several factors to consider, such as cultural, economic and political factors that must be adapted to their organization, they showed that it is possible during the covid-19 pandemic, since they understood the 63% of exporting companies, these results being mainly due to the use of digital marketing. Given this, the present investigation proposed the following objective: Identify digital marketing strategies that improve the promotion of MSMEs in El Oro in the international market in 2022 through documentary review. This research according to its scope is descriptive and of a qualitative nature, the methods that were used for the development of all the research were the historical-logical, synthetic analytical, inductive-deductive, abstraction-concretion and systematic, also empirical methods such as surveys and statistical methods. The materials that were used were scientific articles, books and reports obtained from reliable databases. The selection of the MSME sample was carried out using the non-probabilistic technique: convenience sampling. The results indicate that the MiPymes surveyed are dedicated to the commercialization of bananas and wish to export their products, in addition they have not ventured into international digital promotion, they limit the use of digital marketing to the management of social networks, these being the most used strategies by MiPymes in conjunction with the website. Digital marketing strategies contribute to the promotion of MiPymes in the international market, through the integral management of the company in the different digital platforms. To this end, it is concluded that the digital marketing strategies that contribute the most to the promotion in the international market of agricultural MiPymes in the province of El Oro are social networks, content marketing and organic SEO positioning. Finally, the research was developed in chapters, chapter I is Diagnosis and Conceptualization of the object of study, chapter II is Methodology, chapter III Description and Analysis of results and chapter IV Discussion of results.
A pesar de que el proceso de internacionalización para las MiPymes no es fácil, porque comprende varios factores a considerar como, culturales, económicos y políticos que deben adaptar a su organización, mostraron que es posible durante la pandemia covid-19, puesto que comprendieron el 63% de empresas exportadoras, debiéndose estos resultados principalmente al uso del marketing digital. Ante esto, la presente investigación propuso el siguiente objetivo: Identificar estrategias de marketing digital que mejoren la promoción de las MiPymes de el Oro en el mercado internacional en el 2022 mediante revisión documental. Esta investigación de acuerdo a su alcance es descriptiva y de carácter cualitativa, los métodos que se usaron para el desarrollo de toda la investigación fueron el histórico-lógico, analítico sintético, inductivo-deductivo, abstracción-concreción y sistemático, también métodos empíricos como encuestas y métodos estadísticos. Los materiales que se usaron fueron artículos científicos, libros e informes obtenidos de bases de datos confiables. La selección de la muestra de las MiPymes se realizó mediante la técnica no probabilística: muestreo por conveniencia. Los resultados indican que las MiPymes encuestadas se dedican a la comercialización de banano y desean exportar sus productos, además no han incursionado en la promoción internacional digital, limitan el uso del marketing digital a la gestión de redes sociales, siendo estas las estrategias más usadas por las MiPymes en conjunto con el sitio web. Las estrategias de marketing digital contribuyen a la promoción de las MiPymes en el mercado internacional, mediante la gestión integral de la empresa en las distintas plataformas digitales. A tal efecto, se concluye que las estrategias de marketing digital que más aportan a la promoción en el mercado internacional de las MiPymes agrícolas de la provincia de El Oro, son las redes sociales, el marketing de contenidos y el posicionamiento orgánico SEO. Finalmente, la investigación se desarrolló en capítulos, el capítulo I es de Diagnóstico y Conceptualización del objeto de estudio, el capítulo II es de Metodología, el capítulo III de Descripción y Análisis de resultados y el capítulo IV de Discusión de resultados.
Keywords: MARKETING DIGITAL; MIPYMES; PROMOCION; MERCADO INTERNACIONAL